A Pancreatic Head Tumor Arising as a Duodenal GIST: A Case Report and Review of the Literature - Fabian Bormann; Wolfgang Wild; Hüseyin Aksoy; Pius Dörr; Sanja Schmeck; Matthias Schwarzbach (Case Reports in Medicine)
Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors of the gastrointestinal tract that originate from the intestinal cells of Cajal (ICC) (Fletcher et al., 2002). Only a few cases have been described with extragastrointestinal stromal tumors (Kim et al., 2012; Soufi et al., 2013; Meng et al., 2011). They are often diagnosed as a pancreatic head tumor as they are very difficult to relate to the duodenum with CT, MRI, or ultrasound. We present a case of a sixty-four-year-old woman who presented with abdominal pain and cardialgia for a follow-up examination after breast cancer surgery. On laparotomy there was a 3 × 5 cm hypervascular mass arising from the pancreatic head with macroscopically no attachment to the duodenum. The patient underwent pancreatoduodenectomy (PD) modified after Traverso-Longmire, histopathology proved a duodenal GIST. This case proves that duodenal GISTs can grow invasively into the pancreas and appear as solid pancreas head tumor; therefore, these tumors should be included into differential diagnosis.